The efficiency of the agricultural sector in Poland in the light output-input model = Efektywność sektora rolnego w Polsce w świetle modelu input-output - Czyżewski, Andrzej; Smędzik-Ambroży, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The study turns attention to the use of the input-output model (account of interbranch flows) in macroeconomic assessments of the effectiveness of the agricultural sector. In the introductory part the essence of the account of interbranch flows has been specified, pointing to its historical origin and place in the economic theory, and the morphological structure of the individual parts (quarters) of the model has been presented.
Keywords: model input-output; rachunek przepływów międzygałęziowych; sektor rolny w Polse; efektywność; input-output model; account of interbranch flows; agricultural sector in Poland; effectiveness